Psychometric Properties of Cognitive and Metacognitive Learning Strategies Scale Among Chinese Senior Secondary School Students. (September 2021) - Wang, Faming; Leung, Shing On; Jiang, Chunlian
This study aimed to investigate the validity of the Cognitive and Metacognitive Learning Strategies Scale (CMLSC) for mathematics learning in Chinese context. Exploratory and confirmatory factor analysis, reliability analysis, measurement invariance across gender groups, and criterion-related validity were conducted on 698 Chinese senior secondary school students. Results supported that the adapted CMLSC was reliable and valid. A bifactor model with one general and four specific factors (i.e., rehearsal, elaboration and organization, critical thinking, and metacognitive self-regulation) was found. Residual invariance across gender groups was also achieved. This adapted CMLSC is expected better to understand students' mathematics learning strategies in Chinese culture.